(untitled) (International Journal of Food and Nutritional Sciences, 2023)
This study examined the correlation between body composition and psychological well-being among sedentary undergraduate students in Kerala. A total of 120 students (60 males, 60 females), aged 18–24 years, participated. Body composition was measured using BMI, body fat percentage, and muscle mass, while psychological well-being was assessed using Ryff’s Psychological Well-Being Scale (1989). Pearson’s correlation analysis indicated a significant negative association between body fat percentage and psychological well-being, r(118) = –.62, p = .001, suggesting that higher fat levels were linked to lower well-being. Muscle mass was positively correlated with psychological well-being, r(118) = .56, p = .012, indicating that greater muscle mass predicted better well-being. BMI showed a weak, non-significant negative correlation, r(118) = –.18, p = .064. These findings suggest that specific components of body composition, particularly body fat and muscle mass, are more relevant indicators of psychological well-being than BMI alone. Interventions encouraging physical activity and balanced nutrition are recommended to enhance both physical and mental health among sedentary undergraduates.